2016
DOI: 10.3855/jidc.7939
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial coagulase-negative staphylococci in Belgrade: between Scylla and Charybdis

Abstract: Introduction: Coagulase-negative staphylococci (CoNS) are increasingly resistant nosocomial pathogens. We aimed to analyze the prevalence of CoNS isolates in clinical settings, the evolution of antimicrobial resistance of CoNS, and antibiotic consumption in a hospital. Methodology: This retrospective cohort study was carried out at a tertiary healthcare facility over 17 months. Identification of isolated cultures and antibiotic susceptibility testing were performed using the Vitek2 system. Of 1,217 isolates, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…Longer hospitalisation was confirmed as a risk factor for the occurrence of nosocomial infections caused by multiresistant strains of bacteria. 20,24 Another risk factor for the poor outcome of hospitalised patients, a more common comorbidity, was more prevalent in the sample from BK. This probably contributed to a more frequent occurrence of sepsis caused by G-bacteria, and together with the more frequent use of mechanical ventilation contributed to a significant occurrence of G-lower respiratory tract infections in BK (Table 4).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Longer hospitalisation was confirmed as a risk factor for the occurrence of nosocomial infections caused by multiresistant strains of bacteria. 20,24 Another risk factor for the poor outcome of hospitalised patients, a more common comorbidity, was more prevalent in the sample from BK. This probably contributed to a more frequent occurrence of sepsis caused by G-bacteria, and together with the more frequent use of mechanical ventilation contributed to a significant occurrence of G-lower respiratory tract infections in BK (Table 4).…”
Section: Discussionmentioning
confidence: 98%
“…Demographic characteristics of adult patients at two hospital centres expectedly were different: in BK as a third‐level medical establishment which carries out highly specialised consulting and stationary, educational‐teaching and scientific research activity, patients treated with third‐ and fourth‐generation cephalosporins were older, hospitalisation lasted longer, as the period prior to first isolation of G‐ bacteria. Longer hospitalisation was confirmed as a risk factor for the occurrence of nosocomial infections caused by multiresistant strains of bacteria . Another risk factor for the poor outcome of hospitalised patients, a more common comorbidity, was more prevalent in the sample from BK.…”
Section: Discussionmentioning
confidence: 99%
“…In the previous study performed among patients in a Belgrade tertiary care hospital, susceptibility patterns of coagulase-negative staphylococci were investigated, and the obtained results showed that 70% of the strains were resistant to penicillin, 50% to erythromycin, 40% to clindamycin and 55% to tetracycline [26]. Although similar susceptibility profile was detected in both research, advantages of our investigation is identification of the coagulase-negative staphylococci to the species level and, additionally, determination of the strains sensitivity only to antistaphylococcal antibiotics.…”
Section: Discussionmentioning
confidence: 99%